Rehabilitation interventions for depression symptoms among cancer patients in Palestine: A systematic review - Battat, Maher Mohammad Khalil; Marie, Mohammad (Frontiers in Rehabilitation Sciences, 2022)
Background Depression enhances the disease burden in patients with cancer. Psychological interventions and the rehabilitation of depression are required as a part of palliative care for cancer patients to improve their quality of life and mental health. The aim of the study was to review the literature about depression rehabilitation interventions among patients with cancer in Palestine. Method The electronic databases used: PubMed, Science Direct, Research Gate, and Google Scholar to search for systematic review articles for the review study. Results A total of 23 articles were reviewed, including five from Palestine and five from Arab and Islamic nations. Pharmacological and non-pharmacological interventions used to decrease symptoms of depression and enhance mental health among cancer patients represent the majority of interventions for depression rehabilitation in cancer patients. Interventions for depression rehabilitation among cancer patients in Palestine are only available from the perspective of palliative care, which also involves family education, managing the symptoms of cancer patients, and providing psychological support. Conclusion In Palestine, non-pharmacological interventions, such as psychological interventions, are the primary options for treating and recovering from symptoms of depression. The management of symptoms in cancer patients also has a favorable impact on mental health and recovery from depression. In Palestine, there is a need for improvement in palliative care, particularly interventions for depressive symptoms. The main reason Palestinian patients with cancer have such limited treatment and recovery options are because of Israeli occupation.